Pengantar Sufi: Antara Bidayah dan Nihayah - Sultoni, Agus (Momentum : Jurnal Sosial dan Keagamaan, 2018)
Abstrac: The influence of globalization as it is now requires a change in various aspects of life quickly, demanding that each individual can adapt and follow any changes that occur, even though in reality not all individuals are able to do so that what happens is people or humans face many problems. Not everyone is able to adapt, the result is individuals who store a variety of psychological and physical problems that automatically lead to inner conflicts within themselves, thus an effective way to overcome them is needed.